Young Logan Campbell. - Stone, R. C. J. (Auckland University Press, 2013)
Sir John Logan Campbell is known as the Father of Auckland; he is synonymous with that city. As this first volume of his biography shows, however, he was not particularly enamoured of a pioneering life or of the settlement in which he led it. His purpose in coming to New Zealand and remaining here was to make enough money to live the life of a leisured gentleman in Europe. By the end of this book, he seemed to have achieved his goal. Campbell left, probably, a more comprehensive set of papers than any other early settler. From them, R.C.J. Stone has told a story which not only re.